Evolutionary dynamics of an ancient retrotransposon family provides insights into evolution of genome size in the genus Oryza - Ammiraju, Jetty S. S.; Zuccolo, Andrea; Yu, Yeisoo; Song, Xiang; Piegu, Benoit; Chevalier, Frederic; Walling, Jason G.; Ma, Jianxin; Talag, Jayson; Brar, Darshan S.; SanMiguel, Phillip J.; Jiang, Ning; et al. (Wiley, 2007)
Long terminal repeat (LTR) retrotransposons constitute a significant portion of most eukaryote genomes and can dramatically change genome size and organization. Although LTR retrotransposon content variation is well documented, the dynamics of genomic flux caused by their activity are poorly understood on an evolutionary time scale. This is primarily because of the lack of an experimental system composed of closely related species whose divergence times are within the limits of the ability to detect ancestrally related retrotransposons. The genusOryza, with 24 species, ten genome types, different ploidy levels and over threefold genome size variation, constitutes an ideal experimental system to explore genus‐level transposon dynamics. Here we present data on the discovery and characterization of an LTR retrotransposon family namedRWGin the genusOryza. Comparative analysis of transposon content (approximately 20 to 27 000 copies) and transpositional history of this family across the genus revealed a broad spectrum of independent and lineage‐specific changes that have implications for the evolution of genome size and organization. In particular, we provide evidence that the basal GG genome ofOryza(O. granulata) has expanded by nearly 25% by a burst of theRWGlineageGran3subsequent to speciation. Finally we describe the recent evolutionary origin ofDasheng, a large retrotransposon derivative of theRWGfamily, specifically found in the A, B and C genome lineages ofOryza.